Immobilized dye-decolorizing peroxidase (DyP) and directed evolution variants for hydrogen peroxide biosensing - Barbosa, Catarina (2020)
Immobilized dye-decolorizing peroxidase from Pseudomonas putida MET94 (PpDyP) and three variants generated by directed evolution (DE) are studied aiming at the design of a biosensor for H2O2 detection. Structural properties of the enzymes in solution and immobilized state are addressed by resonance Raman (RR) and surface enhanced RR (SERR) spectroscopy, and the electrocatalytic properties are analyzed by electrochemistry. The wild-type (wt) and 29E4 variant (with E188K and H125Y mutations) represent excellent candidates for development of H2O2 biosensors, since they exhibit a good dynamic response range (1–200 μM H2O2), short response times (2 s) and a superior sensitivity (1.3–1.4 A⋅M−1⋅cm−2) for H2O2, as well as selectivity and long term stability. In contrast to the solution state, 6E10 (with E188K, A142V and H125Y mutations) and 25F6 (with E188K, A142V, H125Y and G129D mutations) variants display much lower activity and are inhibited by high concentrations of H2O2 upon adsorption on an electrode. In terms of sensitivity, the bioelectrodes employing wt PpDyP and 29E4 variant outperform HRP based counterparts reported in the literature by 1–4 orders of magnitude. We propose the development of wt or 29E4 PpDyP based biosensor as a valuable alternative to devices that rely on peroxidases.